2017
DOI: 10.1021/acsmedchemlett.7b00140
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Series of Indazole TRPA1 Antagonists

Abstract: A series of TRPA1 antagonists is described which has as its core structure an indazole moiety. The physical properties and DMPK profiles are discussed. Good exposure was obtained with several analogs, allowing efficacy to be assessed in rodent models of inflammatory pain. Two compounds showed significant activity in these models when administered either systemically or topically. Protein chimeras were constructed to indicate compounds from the series bound in the S5 region of the channel, and a computational d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Pryde et al [ 98 ] reported a series of novel 1 H -indazole derivatives as transient receptor potential ankyrin-repeat 1 (TRPA1) antagonists. The authors investigated the derivatives’s physical properties and in vitro drug metabolism and pharmacokinetics (DMPK) profiles.…”
Section: Biological Applications Of Indazole Derivativesmentioning
confidence: 99%
“…Pryde et al [ 98 ] reported a series of novel 1 H -indazole derivatives as transient receptor potential ankyrin-repeat 1 (TRPA1) antagonists. The authors investigated the derivatives’s physical properties and in vitro drug metabolism and pharmacokinetics (DMPK) profiles.…”
Section: Biological Applications Of Indazole Derivativesmentioning
confidence: 99%
“…[28] Benzazoles are under study as agentsa gainst tuberculosis [29] and some derivatives show antiheparanase activity, [30] which may potentially lead to anticancer treatments. In this work, we focus on indazole [31][32][33][34] and the subtle effect of aromatic bond length alternation. Determination of an accurate molecular structure would allow experimental observation of the effect.…”
Section: Introductionmentioning
confidence: 99%
“…Human-species ortholog chimeras of TRPA1 have proven useful to identify regions of the channel involved in species-dependent compound interactions. Previously, we demonstrated the opossum TRPA1 (oTRPA1) variant which shares 67% amino acid homology with hTRPA1 to be insensitive to carboxamide (Pfizer) and indazole (Novartis) TRPA1 inhibitors (24,25). Likewise, Compound 1 was found to be inactive vs. oTRPA1 ( Fig.…”
Section: Discovery Of a Novel And Selective Trpa1 Small Molecule Inhimentioning
confidence: 92%